2015
DOI: 10.1021/acs.jpca.5b06516
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Photochemistry of N-Salicylidene-p-carboxyaniline Isolated in Solid Argon

Abstract: Infrared matrix isolation spectroscopy and DFT/B3LYP/6-311++G(d,p) calculations have been used to characterize the conformational space of the enol-imine and keto-amine tautomers of N-salicylidene-p-carboxyaniline (SCA) in both their E and Z isomeric forms. Monomers of SCA were isolated in an argon matrix (15 K), which was shown to contain only the most stable conformer of the E-enol isomer of the compound. The matrix-isolated E-enol was then subjected to in situ UV irradiation (λ = 335; 345 nm, provided by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The C–C=N–C dihedral stays in the range ~5–8° in the case of the Z -enol-imine conformers, where the repulsions between the two phenol moieties dominate, and between ~2–4° in the case of the E -enol-imine conformers. This structural feature has already been pointed out before for other aryl Schiff bases [ 26 , 28 , 29 , 30 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The C–C=N–C dihedral stays in the range ~5–8° in the case of the Z -enol-imine conformers, where the repulsions between the two phenol moieties dominate, and between ~2–4° in the case of the E -enol-imine conformers. This structural feature has already been pointed out before for other aryl Schiff bases [ 26 , 28 , 29 , 30 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 75%
“…The four most stable conformers of the E -enol-imine isomer (conformers I, II, V and VI) are more than 38 kJ mol −1 lower in energy than the next conformer in the increasing order of energy (conformer XV). These conformers exhibit an intramolecular hydrogen-bond interaction of the O–H···N type (see Figure 2 ), which leads to the formation of a nearly planar pseudoaromatic six-membered ring where the dihedral angles ϒ and δ are both ~0°, and that is responsible for their stabilization [ 47 ]. Within the two pairs of conformers (I, II) and (V, VI), the main structural difference is the orientation of the non-hydrogen bonded phenolic OH group (the α dihedral angle being near 0 or 180°), while the orientation of the two aromatic rings is the same (i.e., the dihedrals β and ϒ are similar in each pair of conformers).…”
Section: Resultsmentioning
confidence: 99%
“…For deeper insight into the hydrogen-bonding effect on the polymorphic states and isomerization we applied a wide variety of research methods (DFT, X-ray, DSC, NQR, IINS, IR and Raman) in different environments and over a wide temperature range. It is worth noting that the method of matrix isolation was unique in its ability to trace metastable states and help interpret complex reactions [ 11 , 12 , 13 , 14 ]. Moreover, investigations of objects with hydrogen bonding by IINS [ 15 , 16 , 17 , 18 ] and NQR [ 19 , 20 ] techniques are useful.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent reproduction of the experimental data by the calculations shall be highlighted, because frequently the DFT method does not describe hydrogen bonding precisely, which is an essential intramolecular interaction in the case of the experimentally-relevant conformer of the studied molecule. Nevertheless, the functional/basis set used in the present study has been shown to be reliable for infrared spectra predictions for many other intramolecularly-bonded molecules formed exclusively by atoms of the first and second row of the periodic table [26][27][28]. In here, only the assignments for the most prominent characteristic vibrations of PHN will be briefly addressed.…”
Section: Infrared Spectra Of Matrix-isolated Phnmentioning
confidence: 95%